The retirement of the migrant labor force: Pension portability and beyond - Alain Jousten (Center for Economic Studies and ifo Institute (CESifo), 2012)
The specificities of the workforce with a migrant background are often neglected in studies of retirement. Similarly, many studies of migration's impact on pensions often focus on aggregate outcomes - system sustainability or distributive characteristics. The present paper provides a fresh look at the nexus between these two literatures. It discusses the impact of the European social security coordination mechanisms on individual decision-making and on the functioning of social security systems - with a focus on retirement. The paper argues that such effects are non-negligible and are likely to have major policy consequences.
Keywords: F22; H75; J26; J61; 330; pensions; retirement; international migration; social security coordination